Identification and utilization of a new Bacillus amyloliquefaciens XY-1 against Fusarium head blight - Xu, Xiao; Cheng, Yifan; Fang, Zhengwu; Yin, Junliang; Shen, Huiquan; Ma, Dongfang (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB) is a global wheat disease caused by Fusarium graminearu. Biological control is a green environmental protection measures to control this pathogen, however few resources are available at present. In this study, a screenning was performed to identify antagonistic bacteria against FHB from 7 endophytes isolated from roots of wheat. The antagonistic bacterium named XY-1 showed a good antagonistic effect on FHB using dual culture assays. The antagonistic bacterium XY-1 was identified as Bacillus amyloliquefaciens by 16S rDNA sequence, and further antagonistic revealed that XY-1 also has antagonistic activity against Colletotrichum gloeosporioides, Rhizoctonia solani, Sclerotium rolfsii, and Alternaria alternata. Nutrition tests showed that the most suitable carbon source was glucose, and the most suitable nitrogen source was beef extract. The optimum growth temperature was 28 ℃, and the ideal pH value was 7.4. Drug resistance tests showed that XY-1 had strong resistance to Chloramphenicol and Ampicillin Sodium. In vitro antagonism tests showed that strain XY-1 has an antagonistic effect on FHB. It could be a powerful bacteria for the biological control of head blight, which will reduce the harm of FHB to wheat.